CRIMINAL THINKING DITINJAU DARI KELEKATAN KELUARGA BAGI NARAPIDANA KASUS NARKOTIKA UNTUK PEMBINAAN LANJUTAN DI LEMBAGA PEMASYARAKATAN KELAS I SEMARANG - Hadi, Reza Kharisma; Santoso, Iman (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The concept of criminal thinking sees that someone who has a mindset and is involved in criminal lifestyle habits can give rise to antisocial behavior. The criminal mindset originates from a personality that has a unique or distinctive behavioral pattern, such as rationalization thinking, which always gives rise to justification for behavior that is intended to distort the facts. This research was conducted at the Semarang Class I Prison, and the research subjects were correctional inmates with narcotics crime cases, with a sample size of 100 people. The results showed that the attachment variable had a significant effect on the criminal thinking variable in prisoners at the Semarang Class I Penitentiary, and there is a strong relationship between attachment and criminal thinking in prisoners, and the direction of the relationship between the attachment variable and criminal thinking is in the opposite direction (negative correlation), which means that the higher the level of attachment, the lower the level of prisoners' criminal thinking, and conversely, the lower the level of attachment functioning, the higher the criminal thinking. Keywords: Attatchment; Criminal Thinking; Prisoner